The relationship between structural and cyclical features of the EU financial sector - Hanno Stremmel; Balázs Zsámboki (European Central Bank (ECB), 2015)
In this study, we explore the relationship between certain structural features of the banking sectors in EU Member States and the performance of the respective banking sectors over the financial cycle. Using the financial cycle indicator developed by Stremmel (2015), we estimate the impact of the structural features of the banking sector on the amplitude of the financial cycle. Our results suggest that the concentration of the banking sector, the share of foreign banks, the size and stability of financial institutions, the share of foreign currency loans and financial inter-linkages contribute to the amplitude and hence the variability of financial cycles. This study provides important insights into the appropriate design of various structural and cyclical policy instruments as well.
Keywords: E44; E61; G18; G21; G28; 330; banking sector characteristics; financial cycle; financial regulation; financial structure